Mednarodnopravni status Antarktike - Žehelj, Maša (Javna uprava, 2023)
With the exploration of Antarctica, there were also tendencies to appropriate and divide the territory. It was also necessary to legally regulate the field of scientific research in Antarctica. In response to this, negotiations on the conclusion of the Antarctic Treaty followed, which took place in Washington, where the Treaty was also concluded in 1959. Antarctica definitely represents a unique arrangement in international law, it is regulated by the Antarctic Treaty and other treaties that followed. Given such a treaty arrangement, the Antarctic Treaty would, as is customary, only bind its signatories. Even in international law, the principle applies that the provisions of the contract may neither harm nor benefit third parties, i.e. countries that are not signatories. The Vienna Convention on the Law of Treaties stipulates that an international treaty cannot impose obligations or confer rights on a third country without its consent. Considering this, the Treaty could only have effects vis-a-vis the contracting parties, but international law recognizes a special case of treaties in favour of third parties, which establish an "objective regime" that operates erga omnes, and the Treaty also belongs to this "objective regime" framework about Antarctica, or the entire legal regime of Antarctica, thus creating erga omnes effects.
Keywords: Antarctic Treaty; Antarctica; international legal status of Antarctica; Mednarodno pravo; objective regime; Pogodba o Antarktiki; politična geografija; The Antarctic Treaty System